Performance Improvement Strategy Through the Business Environment, Product Innovation and Competitive Advantage - Aswad Fahruddin; Abd. Rahman Kadir; M. Sobarsyah (Digital Economy and Digital Transformation Review, 2023)
In an an increasing number of competitive surroundings and clients who are increasingly critical in choosing merchandise, corporations are required to be more progressive in generating a product. there are many competitive strategies to turn out to be market winners, consisting of product innovation techniques. Product development or product innovation is very crucial in cutting-edge market competition. All efforts, the energy possessed via the organization, is directed to produce value as anticipated, because higher effects imply having introduced fee as compared to competition. what is the relationship between commercial enterprise surroundings on SME overall performance thru variables product innovation and competitive benefit? There are nonetheless few researchers who find out this query. research to study the have an effect on of the commercial enterprise surroundings, product innovation and aggressive gain at the performance of SMEs. This kind of studies is a survey. The populace on this look at is all SMEs in Makassar town. The sampling method is easy random sampling with a complete of 300 respondents. The statistical technique used is path analysis. The effects of the studies show that: (1) there's a effective have an impact on of the enterprise surroundings on product innovation., (2) there may be a effective have an effect on of the business environment on competitive advantage., (three) there may be a wonderful impact of product innovation on SME overall performance., (five) there is a high quality effect of competitive gain on SME performance. The practical implications are; (1) SMEs should continue to improve their business orientation by making clearer visions and business goals by preparing longer-term business plans and clearer., (2) Increasing business learning and sustainable competitive advantage by continuously seeking new information, especially from sources of formal activities.